EVALUATION OF THE EFFECTS OF FTO AND ENVIRONMENT ON BODY MASS INDEX (BMI) IN A MULTI-ETHNIC COHORT OF OLDER ADULTS. (16th November 2018) - Thompson, M; Pirkle, C; Wu, Y; Youkhana, F; Cheng, I; Wilkens, L; Le Marchand, L
Abstract: Genetic predisposition may increase the risk of obesity. Many genome-wide association studies (GWAS) document associations between the FTO gene and obesity. Both genes and the environment interact across the life-course to influence body mass, but limited research examines both factors simultaneously. Moreover, studies of the genetic basis of obesity are rare among ethnic minority groups. Through a GWAS of 5211 participants of the Multiethnic Cohort (MEC), who were 42 years and older at baseline, the single nucleotide polymorphism (SNP) rs1421085 in FTO was replicated as a risk factor for greater mean body mass index (BMI). MEC contains large samples of Blacks, Latinos, Japanese, Native Hawaiians, and Whites from Hawaii and Los Angeles. Stratified by race/ethnicity, we conducted polynomial regressions to examine the cross-sectional association between life-course and social variables (age, sex, family size, number of children, place of birth, marital status, education), health behaviors (smoking, alcohol consumption, diet, exercise, and sleep), and rs1421085 on BMI. In fully adjusted models, SNP rs1421085 was statistically associated with greater BMI in Japanese (β 0.55, 95%CI 0.26–0.83) and Native Hawaiians (β 0.70, 95%CI 0.11–1.28), but not in Blacks, Latinos, and Whites. Physical activity was the only behavior associated with BMI across all models (β -1.66 in Native Hawaiians to -1.19 in Latinos). Distinct risk factors for higher BMI were observed in each racial/ethnic group. Overall, results indicate unique genetic and environmental risk factors by racial/ethnic category, but also reinforce the importance of physical activity for maintaining a healthy BMI.